23=8x

Simple and best practice solution for 23=8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23=8x equation:


Simplifying
23 = 8x

Solving
23 = 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
23 + -8x = 8x + -8x

Combine like terms: 8x + -8x = 0
23 + -8x = 0

Add '-23' to each side of the equation.
23 + -23 + -8x = 0 + -23

Combine like terms: 23 + -23 = 0
0 + -8x = 0 + -23
-8x = 0 + -23

Combine like terms: 0 + -23 = -23
-8x = -23

Divide each side by '-8'.
x = 2.875

Simplifying
x = 2.875

See similar equations:

| 5v^2-10v-40=0 | | (2x+1)-2(x-5)+6=3x(x+1)+(x-1)+23 | | 4(7v-2)-7=4(1+7v) | | 4k(3+k)=-(2k+3) | | -9(z+5)=0 | | -9(z+6)=0 | | x(x-3)-x(x+5)+6=-2 | | 1-7n-2n=-8 | | 7-a=15a-2a | | -16x^2+3x+1.3=0 | | (23+5x)=(14x-3) | | 3(n-8)=4(n+2) | | (2n+5)(2n+3)=0 | | R=5x+43 | | (4g+7)+(7g+2)= | | 23+5x=14x-3 | | 4(c-3)+5=2c+3 | | 6(m+1)=3m-3 | | -3(a+4)=6 | | -g+6+2g=4g+4 | | 6x+7=2x-13 | | 12-1.7x=4.15 | | (x+1)+2(x-3)-5=(x+2)-(x+3)+2 | | ln(5x+3)=4 | | 27-3(2x+3)=2(1-3x) | | 7-n-6=-13+6n | | 12x^2+9x-20=0 | | 5(2.6x+3.9)=5 | | cos(2x)-5cosx+3=o | | .5x+7=2x+14 | | 1-4=7 | | 18-8(x+2)=2(x-9) |

Equations solver categories